Education and employment outcomes for people with disability - Dockery, Alfred Michael; Twigger, M. (Centre of Full Employment and Equity, 2010)
Disability is a heterogeneous condition that affects 20% of Australians across a broad spectrum of conditions. Despite the enactment of the Disability Discrimination Act of 1992 for the elimination of discrimination in a number of key areas research indicates that very little has changed for this significant proportion of the population. The 2003 Survey of Disability, Ageing & Carers (SDAC) found that disabled Australians have significantly lower levels of education, higher levels of unemployment and lower gross personal household income than that of persons without disability. Of further concern, analysis of ABS data shows an increasing trend in disability rates among young people between 1981 and 2003, while levels of high school graduation for disabled persons fell. This paper builds on past research in education and subsequent employment outcomes for disabled Australians. Using data from the ABS SDAC we examine changes in employment opportunity for disabled people by severity of their disability and the role that access to education has played in reducing labour market disadvantage.